Study of the Optical properties for CdS before and after irradiated by CO2 laser for different exposure times - Najat A. Dahham (Tikrit Journal of Pure Science, 2023)
Cadmium sulphide (CdS) thin films were deposited on glass substrates  using thermal vacuum evaporation technique at pressure (10-6) Torr at room temperature  then samples irradiated by CO2 laser of power (1 watt) and wave length (10.6) μm at distance 10 cm from the source during different exposure times (3, 5, 10, 15) sec. The absorbance spectra was recorded using UV-visible spectrophotometer .Optical  properties such as  transmission , reflection ,absorption coefficient (α), optical band gap (Eg), extinction coefficient (K), refractive index (n), and complex  dielectric constants  (er&ei) were evaluated from absorbance spectra. The results shows that the laser irradiation cause  increased in reflectance R, absorption coefficient a, the extinction coefficient K, the refractive index n and the real part and imaginary part of dielectric constant while irradiation cause decrease in the transmittance T and the value of the energy gap Eg.